LEMAHNYA PERILAKU PELAYANAN PUBLIK DIDALAM REFORMASI BIROKRASI DEWASA INI - Nanik Pujiastuti (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2022)
Inner country effort reach the goal, of course need device country called _ government and his government . In Thing this , the government on the truth is give service to society . For that 's bureaucracy no held for serve herself alone , but serve Public as well as create condition every member Public for develop ability and his creativity.in line with fast development era and the more the complex problem faced _ by country , then has there is development maintenance marked government _ with existence shift paradigm maintenance government from rule government to good governance paradigm . Because that , task main in skeleton strengthening existence government including government area is create government which _ political acceptable , legally law effective , and by administrative efficient .